PENGARUH MOTIVASI, KEPEMIMPINAN, BUDAYA KERJA DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI PT. PLN (PERSERO) KANTOR REGIONAL WILAYAH RIAU DAN KEPULAUAN RIAU - Sinaga, Winda Novelya (Jurnal Tepak Manajemen Bisnis, 2014)
Effect of Motivation, Leadership, Work Culture, and Passion to Employeeâs Performance of PT. PLN(Persero) Region of Riau and Riau Islands.This studyâs intend is to analyze the motivation, leadership, workculture and passion of the employeeat PT. PLN (Persero) Region of Riau and Riau Islands towards theirperformance, either partially or simultaneosly.This study sampled 103 Employees PT. PLN (Persero) Region of Riau and Riau Islands.The results represent thatsimultaneous variables of motivation, leadership, work culture and passion significantly affect the performanceof employees at PT .PLN (Persero) region of Riau and Riau Islands. It is showed that the value of t-Hitung > t-Tabel at significant level Ã¡ = 0.05, the value of F-Hitung > F-Tabel and the great influence given by thatindependent variables on the dependent variable of determination (R2) 53.30% while 46.70% affected by othervariables. Partial tests represent that t-value on motivation, leadership, and passion is greater than t-table.Meaning that motivation, leadership and passion have the partial effect on performance, while t-hitung of thework culture is smaller than t-table, means that the work culture does not have partial effect on performance.This research partially shows that motivation, leadership and passion have relationship and influence on theemployeeâs performance and have a relationship and the most dominant influence on their performance, butwork culture does not havethe influence on it. The implication of this research is the research conductedongovernment agencies with a large number of samples. It is necessarilly that in the future this research shouldexamine the private agency that has many population and compound or insert other variables that can affect theperformance of employees such as planning, supervision and working environment so that the value of thecoefficient determination can be varied significantly.Keywords : motivation, leadership, work culture, passion and performance.